Divulgação do Museu Fotográfico Irmão Ademar da Rocha do Município de Faxinal do Soturno/RS - Leonardi, Rosangela (2023)
This study aims to promote the Irmão Ademar da Rocha Photographic Museum, a memory and identity space in the municipality of Faxinal do Soturno, located in Quarta Colônia, Rio Grande do Sul, and brings with it a contextualization of the historical and social formation of the municipality, emphasizing the influence of Italian immigrants in the customs and traditions left to descendants. The museum takes care of photographic records as a link between the past, present and future, representing identity and local memory. The research has the general objective of publicizing the Museum through the elaboration of physical and digital material, aiming at the dissemination of memories and local records, promoting the recognition of its historical and cultural value, through the appreciation of memories of a people, showing its importance in the process of patrimonialization of the collections and the benefits of the dissemination of memories and local registers. The methodology, of an applied nature, through a qualitative approach, sought to focus on the relevance of this heritage asset for the community. To base the study, research was used in different bibliographic, documentary and scientific sources, in photographs and in sites that take care of the subject. The product achieved, Guide to the Museum, is based on the dissemination of the museum as a memory space, aiming to contribute to the appreciation of the faxinalense and regional identity through the insertion in a heritage education policy that encourages the recognition and appreciation of the cultural assets of significantly, reinforcing the sense of belonging of the local community, making it the protagonist of the historical process, bringing visibility to it, serving as a tourist and cultural attraction. The research is the result of the Professional Master's Degree in Cultural Heritage, belonging to the Concentration Area in Architecture and Material Heritage, linked to the Preservation and Material Heritage Research Line, made possible as a result of the Geopark Quarta Colônia.